(untitled) (Journal of Science Foundation, 2016)
Background: Gingival Condition is an important issue in provisional crown in fixed prosthodontics treatment. Objective: The purpose of the present study was to find out any change of gingival condition after insertion of self-cured and heat-cured acrylic resin provisional crown. Methodology: This prospective comparative study was carried out in the Department of Prosthodontics, Faculty of Dentistry, Bangabandhu Sheikh Mujib Medical University, Dhaka from July 2014 to June 2015 for a period of one year. Patients who were treated with full veneer crown in the department of Prosthodontics, Faculty of Dentistry, BSMMU, and also their provisional crown were prepared with self-cured and heat-cured acrylic resin. Patients were divided into two groups named as group A and group B. Group A patients were treated with self-cured acrylic resin provisional crown. Group B patients were treated with heat-cured acrylic resin provisional crown. Patient was examined and clinical finding such as gingival condition, color change and burning sensation of gingival tissue were recorded on the data collection sheet. Data were collected on the day of insertion and on recall visit 3rd day and 7th day. Result: A total number of 48 patients were recruited of which 24 patients were in group A and the rest 24 patients were in group B. At the day of insertion the gingival condition of all the patients in group A and B were in grade 0. In day 3, the changes of gingival condition of grade 0 is significant (p=0.009). At the 7th day, grade 0 and I were not significantly change. Conclusion: Both heat-cured acrylic resin provisional crowns and self-cured acrylic resin provisional crowns maintain healthy gingiva in the oral cavity. Journal of Science Foundation, 2015;13(2):31-35 DOI: http://dx.doi.org/10.3329/jsf.v13i2.27930